IL17/IL17RA as a Novel Signaling Axis Driving Mesenchymal Stem Cell Therapeutic Function in Experimental Autoimmune Encephalomyelitis - Kurte, Mónica; Luz-Crawford, Patricia; Vega-Letter, Ana María; Contreras, Rafael A.; Tejedor, Gautier; Elizondo-Vega, Roberto; Martinez-Viola, Luna; Fernández-O’Ryan, Catalina; Figueroa, Fernando E.; Jorgensen, Christian; Djouad, Farida; Carrión, Flavio (Frontiers in Immunology, 2018)
Abstract The therapeutic effect of mesenchymal stem cells (MSCs) in multiple sclerosis (MS) and the experimental autoimmune encephalomyelitis (EAE) model, has been well described. This effect is, in part, mediated through the inhibition of IL17-producing cells and the generation of regulatory T cells. While proinflammatory cytokines such as IFNγ, TNFα and IL-1β have been shown to enhance MSCs immunosuppressive function, the role of IL17 remains poorly elucidated. The aim of this study was therefore to investigate the role of the IL17/IL17R pathway on MSCs immunoregulatory effects focusing on Th17 cell generation in vitro and on Th17-mediated EAE pathogenesis in vivo. In vitro, we showed that the immunosuppressive effect of MSCs on Th17 cell proliferation and differentiation is partially dependent on IL17RA expression. This was associated with a reduced expression level of MSCs immunosuppressive mediators such as VCAM, ICAM and PDL-1 in IL17RA-/- MSCs as compared to wild type (WT) MSCs. In the EAE model, we demonstrated that while WT MSCs significantly reduced the clinical scores of the disease, IL17RA-/- MSCs injected mice exhibited a clinical worsening of the disease. The disability of IL17RA-/- MSCs to reduce the progression of the disease paralleled the inability of these cells to reduce the frequency of Th17 cells in the draining lymph node of the mice as compared to WT MSCs. Moreover, we showed that the therapeutic effect of MSCs was correlated with the generation of classical Treg bearing the CD4+CD25+Foxp3+ signature in an IL17RA-dependent manner. Our findings reveal a novel role of IL17RA on MSCs immunosuppressive and therapeutic potential in EAE and suggest that the modulation of IL17RA in MSCs could represent a novel method to enhance their therapeutic effect in MS.